Historical analysis of mangrove leaf traits throughout the 19th and 20th centuries reveals differential responses to increases in atmospheric CO2. Issue 11 (16th September 2014) - Reef, Ruth; Lovelock, Catherine E
Abstract Aim To reconstruct the historic response of two dominant mangrove species to increases in atmospheric CO2 over the past two centuries. Location Indo‐Pacific. Methods We use a novel approach to assess plant responses to rising atmospheric CO2 concentrations by measuring leaf traits of herbarium specimens of two dominant and widespread mangrove species. Results Leaf traits were correlated with atmospheric CO2 concentration and latitude, but not with rainfall or the multidecadal multivariate El Niño–Southern Oscillation index. Rhizophora stylosa and Avicennia marina exhibited significant differences in their response to elevated CO2. Increases in atmospheric CO2 concentrations over the past 165 years have led to a corresponding rise in photosynthetic carbon gain by the widespread mangrove A. marina, but not by R. stylosa. Main conclusions CO2 fixation is at the heart of plant energy acquisition, global primary productivity and CO2 sequestration. Given that atmospheric CO2 concentrations have been rapidly rising for the past two centuries, surprisingly few datasets have examined the long‐term response of trees to rising CO2. Our results suggest changes to interspecific interactions, nutrient cycling and carbon sequestration in these globally significant forests are expected as CO2 concentrations continue to increase.